2018
DOI: 10.1007/978-1-4939-7634-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of External Guide Sequences’ (EGS) Efficiency as Inducers of RNase P-Mediated Cleavage of mRNA Target Molecules

Abstract: RNase P is a ribozyme consisting of a catalytic RNA molecule and, depending on the organism, one or more cofactor proteins. It was initially identified as the enzyme that mediates cleavage of precursor tRNAs at the 5'-end termini to generate the mature tRNAs. An important characteristic of RNase P is that its specificity depends on the structure rather than the sequence of the RNA substrate. Any RNA species that interacts with an antisense molecule (called external guide sequence, EGS) and forms the appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Also, the compound must efficiently penetrate the cells once it reached the site of infection. Promising but still preliminary results have been obtained testing conjugates between nuclease resistant hybrid locked nucleic acids (LNA)/DNA oligomers and the cell penetrating peptide (RXR) 4 XB (where R stands for arginine, X for 6-aminohexanoic acid, and B for beta-alanine) ( Jackson et al, 2016 ; Jani et al, 2018 ). Although previous reports indicate that antisense compounds containing LNA and DNA nucleotides show low toxicity ( Wahlestedt et al, 2000 ), once a specific compound is identified as a candidate for treatment of A. baumannii infections, its cytotoxicity will have to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the compound must efficiently penetrate the cells once it reached the site of infection. Promising but still preliminary results have been obtained testing conjugates between nuclease resistant hybrid locked nucleic acids (LNA)/DNA oligomers and the cell penetrating peptide (RXR) 4 XB (where R stands for arginine, X for 6-aminohexanoic acid, and B for beta-alanine) ( Jackson et al, 2016 ; Jani et al, 2018 ). Although previous reports indicate that antisense compounds containing LNA and DNA nucleotides show low toxicity ( Wahlestedt et al, 2000 ), once a specific compound is identified as a candidate for treatment of A. baumannii infections, its cytotoxicity will have to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Both fractions were combined and incubated for 90 min at 37°C. The reaction was stopped by heating and subjected to phenol/chloroform extraction followed by ethanol precipitation as described before ( Jani et al, 2018 ). The products were resuspended in 1 volume of gel loading buffer and analyzed by 6% denaturing TBE-PAGE or GTG-PAGE ( Soler Bistue et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…An LNA/DNA gapmer designed to target the amikacin resistance aac(6 ′ )-Ib gene mRNA and elicit cleavage by the endogenous RNase P [4] was covalently bound to a CPP. The compound produced a modest reduction in the levels of resistance to amikacin in a clinical Acinetobacter baumannii isolate [78]. LNA-containing compounds were also delivered inside target cells using nanoparticles [79].…”
Section: Lna—a Brief Overviewmentioning
confidence: 99%
“…However, combinations of other kinds of antibiotics with inhibitors of resistance are still in experimental stages [99,104]. In particular, antisense inhibition of antibiotic resistance genes was explored using oligomers of different natures that interfere with the expression of resistance by different mechanisms [41,42,78,98,101,105,106,107,108]. The aac(6 ′ )-Ib gene codes for an acetyltransferase responsible for the resistance to amikacin and other aminoglycosides found in the vast majority of AAC(6′)-I-producing Gram-negative clinical isolates [104,109].…”
Section: Bnancmentioning
confidence: 99%
“…Furthermore, conjugation of a selected DNA/LNA hybrid oligomer to the cell permeabilizing peptide (RXR)4XB reduced the levels of resistance to amikacin of an aac(6')-Ib-containing Acinetobacter baumannii clinical isolate[34,71]. Assessment of isosequential hybrid oligomers containing BNA NC in place of the LNA residues showed that they failed to elicit cleavage of the mRNA at levels comparable to those found when testing LNA/DNAs[34].…”
mentioning
confidence: 96%